2021
DOI: 10.1096/fj.202001904rr
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated miRNAs in bone cells of patients with Gorham‐Stout disease

Abstract: Gorham‐Stout disease (GSD) is a very rare disease characterized by increased bone erosion with angiomatous proliferation. The mechanisms underlying this disorder have not been deeply investigated. Due to its rarity, no guidelines are currently available for treatment and management of GSD. We recently evaluated the cellular alterations of the bone remodeling in patients showing that osteoclast precursors displayed increased ability to differentiate into osteoclasts and that affected osteoclasts resorb bone mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…There are no biomarkers available for GSD, but in some studies miRNAs and serum biomarkers were reported as possible biomarkers. There are studies that show changes in miRNAs in GSD, suggesting that these molecules could be used as potential biomarkers in GSD [ 27 ]. Some of these molecules of miRNAs (miR-1246, miR-137, and miR-1) are correlated with angiomatous proliferation and regulation of osteoclastogenesis and altered osteoclast morphology resulting in a more motile phenotype [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no biomarkers available for GSD, but in some studies miRNAs and serum biomarkers were reported as possible biomarkers. There are studies that show changes in miRNAs in GSD, suggesting that these molecules could be used as potential biomarkers in GSD [ 27 ]. Some of these molecules of miRNAs (miR-1246, miR-137, and miR-1) are correlated with angiomatous proliferation and regulation of osteoclastogenesis and altered osteoclast morphology resulting in a more motile phenotype [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that show changes in miRNAs in GSD, suggesting that these molecules could be used as potential biomarkers in GSD [ 27 ]. Some of these molecules of miRNAs (miR-1246, miR-137, and miR-1) are correlated with angiomatous proliferation and regulation of osteoclastogenesis and altered osteoclast morphology resulting in a more motile phenotype [ 27 ]. Other miRNA molecules (miR-204-5p, miR-378a-3p, miR-615-3p, and miR-204-5p) play a role in inhibiting osteoblast differentiation and are elevated in GSD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation to determine the presence of lymphatics in bone could be due to abnormal LEC migration during development. This hypothesis could explain the reason why there are CLA subtypes that only affect trabecular bone (GLA/KLA) while also justifying the abnormal inherent characteristics found in bone cells isolated from GSD patients [ 54 , 67 , 68 , 92 , 93 , 94 ]. Further research focused on understanding the source of invading lymphatics might facilitate patient diagnosis and development of new treatments.…”
Section: Lymphatic Bone Invasionmentioning
confidence: 99%
“…Ten patients were recruited by the Rare Diseases and Medical Genetics Unit of Bambino Gesù Children's Hospital (OPBG). The description of nine patients was previously reported (Rossi et al, 2021). A 12 years old female patient with swelling of the frontal bone, osteolysis of frontal and parietal bone, vertebrae and left scapula has been recently recruited for this study (Supplementary Table 1).…”
Section: Patientsmentioning
confidence: 99%